2021
DOI: 10.3390/life11101000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of IL-18 and Soluble Cell Adhesion Molecules in the Gingival Crevicular Fluid as Novel Biomarkers of Psoriasis

Abstract: Psoriasis is a chronic immunoinflammatory skin disease. Although its diagnosis is clinical, differences in the appearance and severity of lesions pose a challenge for clinicians worldwide. The use of accessible biomarkers for psoriasis could aid in the early diagnosis and treatment of the disease. To date, evidence on the analysis of gingival crevicular fluid (GCF) molecules as novel, accessible, and reliable biomarkers for psoriasis is limited. This cross-sectional study compared the GCF levels of IL-18, solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…The stimulation of the human keratinocyte cell line - HaCaT with ultraviolet B radiation upregulated the production of IL-18 ( 198 ). Several studies have strongly indicated that IL-18 is a strong biomarker for clinical psoriasis symptoms ( 139 , 140 , 199 ). Overall, these data may indicate the potential role of IL-18 in psoriasis therapy.…”
Section: Pathophysiological Autoimmune Conditions Associated With Il-18mentioning
confidence: 99%
“…The stimulation of the human keratinocyte cell line - HaCaT with ultraviolet B radiation upregulated the production of IL-18 ( 198 ). Several studies have strongly indicated that IL-18 is a strong biomarker for clinical psoriasis symptoms ( 139 , 140 , 199 ). Overall, these data may indicate the potential role of IL-18 in psoriasis therapy.…”
Section: Pathophysiological Autoimmune Conditions Associated With Il-18mentioning
confidence: 99%
“…Therefore, according to these studies, rosacea could cause changes in the composition of proteins in bodily fluids. Our group also reported that psoriasis and atopic dermatitis could influence the GCF’s concentrations of cytokines and MMP, respectively [ 25 , 36 ]. Since rosacea shares specific inflammation mechanisms with psoriasis and atopic dermatitis [ 37 , 38 ], we hypothesized that rosacea might also modify the protein composition in the GCF.…”
Section: Discussionmentioning
confidence: 99%
“…A trained lab analyst made the GCF analyses using pooled samples from each individual and prepared the specific elution by adding forty microliters of protein buffer solution to each tube. The dilutions were then incubated at 4 °C for thirty minutes and immediately centrifuged at 12,000× g for five minutes at the same temperature [ 36 ]. The procedure was repeated twice to optimize the isolation of proteins.…”
Section: Methodsmentioning
confidence: 99%
“…Volunteers diagnosed with AD and healthy controls (C) were conveniently enrolled between March and December 2018 at the International Center for Clinical Studies (CIEC) in Santiago, Chile, and the Dental Clinic of the Faculty of Dentistry at UNAB in Santiago, Chile, respectively. Eligible subjects met the following inclusion criteria: (i) age over 18 years and (ii) possession of at least twelve functional teeth, excluding third molars [25,[64][65][66]. In accordance with the study design, the following exclusion criteria were applied: (i) individuals with systemic or dermatological disorders other than AD, especially those characterized by immunoinflammatory dysregulation (such as diabetes, lupus, psoriasis, and rheumatoid arthritis, among others) [25,64], (ii) individuals who had received antibiotics, anti-inflammatory or immunomodulatory drugs within the past three months, (iii) patients who had undergone chemo-or radiotherapy in the previous twelve months, (iv) pregnant females, and (v) patients who had received treatment for AD or periodontitis in the last three months [25,64].…”
Section: Participantsmentioning
confidence: 99%